2007
DOI: 10.1345/aph.1k347
|View full text |Cite
|
Sign up to set email alerts
|

Safety Concerns with Fluoroquinolones

Abstract: Clinicians should be aware of possible alterations in blood glucose, QTc interval prolongation, seizures, phototoxicity, tendinopathy, or CDAD with the use of any fluoroquinolone, especially in patients with other risk factors for these conditions. Clinicians should closely monitor for these adverse effects and appropriately adjust doses to minimize these risks. To provide safe treatment for patients needing antibiotic therapy, an assessment of the risk-benefit ratio may be warranted in the decision to use a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
108
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(112 citation statements)
references
References 6 publications
1
108
0
3
Order By: Relevance
“…A single-dose crossover study in healthy volunteers showed a reduction in the elimination rate of gatifloxacin resulting in a 14% increase in the area under the concentration time curve to infinity (AUC 0 -ϱ ) when it was given together with rifampin, isoniazid, and pyrazinamide (8). Reports of dysglycemia related to the use of gatifloxacin in elderly patients with renal insufficiency (9,10,11,12) have raised concerns that pharmacokinetic interactions may lead to an increased risk of toxicity related to higher gatifloxacin exposure. On the other hand, in vitro and in vivo studies suggest a target ratio of Ն125 for the free drug area under the concentration versus time curve to MIC (fAUC/MIC) for maximal bactericidal effect and prevention of resistance to fluoroquinolones (13,14).…”
mentioning
confidence: 99%
“…A single-dose crossover study in healthy volunteers showed a reduction in the elimination rate of gatifloxacin resulting in a 14% increase in the area under the concentration time curve to infinity (AUC 0 -ϱ ) when it was given together with rifampin, isoniazid, and pyrazinamide (8). Reports of dysglycemia related to the use of gatifloxacin in elderly patients with renal insufficiency (9,10,11,12) have raised concerns that pharmacokinetic interactions may lead to an increased risk of toxicity related to higher gatifloxacin exposure. On the other hand, in vitro and in vivo studies suggest a target ratio of Ն125 for the free drug area under the concentration versus time curve to MIC (fAUC/MIC) for maximal bactericidal effect and prevention of resistance to fluoroquinolones (13,14).…”
mentioning
confidence: 99%
“…Arthropathy and tendon disorders have been reported in patients being treated with, or following treatment with, fluoroquinolones; 65,[116][117][118][119][120] estimates of the prevalence of these events vary. In a case-control study, the event rate of Achilles tendonitis and rupture associated with fl uoroquinolones was 3.2/1000 patient treatment-years.…”
Section: Tendonopathymentioning
confidence: 99%
“…They are widely used in primary care and hospital settings resulting in being the "first choice" in the therapy of respiratory, genitourinary, skin and soft tissue infections [2]. These drugs have shown good tissue penetration and excellent oral bioavailability [3].…”
Section: Introductionmentioning
confidence: 99%